2021
DOI: 10.1161/circresaha.120.318149
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast Deficiency of LSD1 Alleviates TAC-Induced Heart Failure

Abstract: Rationale: Histone lysine specific demethylase 1 (LSD1) is an important epigenetic anti-tumor drug target, whose inhibitors are currently in phase Ⅰ/Ⅱ clinical trials. However, the potential side effects of LSD1 inhibition in the progress of cardiac remodeling to heart failure remain to be investigated. Objective: To evaluate the roles of myofibroblast- or cardiomyocyte-specific LSD1 deficiency in pressure overload-induced cardiac remodeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…For picrosirius red staining, heart sections were incubated with picrosirius red solution (Abcam, ab150681) at RT for 1 hour as described previously. 26 Four to five randomly selected fields (magnification, ×200) were examined for collagen volume fraction analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For picrosirius red staining, heart sections were incubated with picrosirius red solution (Abcam, ab150681) at RT for 1 hour as described previously. 26 Four to five randomly selected fields (magnification, ×200) were examined for collagen volume fraction analysis.…”
Section: Methodsmentioning
confidence: 99%
“…34 LSD1 inhibition has been reported to reduce the supernatant TGFβ1 secretion in Ang II-induced cardiac myofibroblasts, implying the possible involvement of LSD1 in TGFβrelated fibrotic response. 35 We found that the treatment with ORY-1001 decreased the expression of TGF-β1 mRNA in UUO kidneys compared to that in the vehicletreated kidneys (Figure S7A). In addition, targeting LSD1 with ORY-1001 or siRNA also decreased the expression of TGF-β1 mRNA in renal fibroblasts (Figure S7B,C).…”
Section: Discussionmentioning
confidence: 84%
“…The activation of renal fibroblasts, the main effector cells in fibrogenesis following kidney injury, mainly contribute to the increased synthesis of matrix components.TGF‐β1 has been reported to play a central role in mediating renal fibroblast activation and the deposition of excessive ECM in response to renal injury 34 . LSD1 inhibition has been reported to reduce the supernatant TGFβ1 secretion in Ang II‐induced cardiac myofibroblasts, implying the possible involvement of LSD1 in TGFβ‐related fibrotic response 35 . We found that the treatment with ORY‐1001 decreased the expression of TGF‐β1 mRNA in UUO kidneys compared to that in the vehicle‐treated kidneys (Figure S7A).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KDM1A −/− cardiac cells display improper upregulation of genes related to lipid metabolism. Relevantly, hyperlipidemia is associated with cardiac fibrosis ( Ma et al., 2013 ), and a recent study reported increased cardiac fibrosis in KDM1A −/− cardiac cells in vivo ( Huo et al., 2021 ). Therefore, we could speculate that KDM1A ablation promotes cardiac tissue fibrosis by the upregulation of cholesterol and lipid-related pathways.…”
Section: Discussionmentioning
confidence: 99%